Retakaful pool framework for Takaful operators in Malaysia: Experts' opinions - Htay, Sheila Nu Nu; Hamat, Mustapha; Wan Ismail, Wan Zambri; Salman, Syed Ahmed (Maxwell Scientific Organization, 2014)
alaysia is trying to position itself as a hub of Islamic finance and the government is promoting the Islamic finance industry. Takaful industry is rapidly increasing however, Retakaful industry is not catching up with the dynamic and complex needs of Takaful industry. In addition, the existence of the limited number of Retakaful operators causes Takaful operators not much bargaining power in negotiating the Retakaful agreement and Takaful operators have no option except to follow the requirements set by Retakaful operators. Thus, this study intends to propose framework for Retakaful pool mechanism by seeking the opinions of experts in Malaysia. By introducing Retakaful pool among the Takaful operators, it will create mutual and friendly business environment among them and reduce dependency on Retakaful operators. In addition, the experts believe that Retakaful pool will bring more benefit to the Takaful operators, compared to the traditional Retakaful method, i.e., engaging with Retakaful operators